1997
DOI: 10.1086/304480
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence for Some Gamma‐Ray Bursts Consistent with Primordial Black Hole Evaporation

Abstract: Previously we identiÐed some short burst events from the BATSE 1B catalog that were consistent with an origin of primordial black hole evaporation at the quark-gluon phase transition. We showed that these events are also consistent with arising from a homogeneous spatial distribution. Recently the PHEBUS group has also indicated that the short bursts are consistent withIn this paper V /V ' D 1/2. we describe the results of the study of the BATSE 3B catalog shape that conÐrm the results from BATSE 1B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 36 publications
3
69
0
1
Order By: Relevance
“…4B indicates a <V/V max > much less than 0.5 consistent with the same mean values for the L (long) events, which is now widely interpreted as being due to the cosmological sources for those GRBs. It is probable that the M events are also from cosmological sources; however the S events appear to come from local sources .We note that the short bursts are strongly consistent with a spectrum, indicating C 3/2 p a Euclidean source distribution, as was shown previously (D. Cline et al (1997). In the medium time duration (from 100 ms to 1 s), the ln N ln S distribution seems to be non-Euclidean.…”
Section: The V/v Max Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…4B indicates a <V/V max > much less than 0.5 consistent with the same mean values for the L (long) events, which is now widely interpreted as being due to the cosmological sources for those GRBs. It is probable that the M events are also from cosmological sources; however the S events appear to come from local sources .We note that the short bursts are strongly consistent with a spectrum, indicating C 3/2 p a Euclidean source distribution, as was shown previously (D. Cline et al (1997). In the medium time duration (from 100 ms to 1 s), the ln N ln S distribution seems to be non-Euclidean.…”
Section: The V/v Max Discussionsupporting
confidence: 86%
“…We have carried out an extensive study of these GRBs (Cline et al 1999(Cline et al , 1997, and have concluded that:…”
Section: Introductionmentioning
confidence: 99%
“…And then there are primordial black holes, whose decays have long been sought and not seen at gammaray or other wavelengths. Belyanin et al (1996, modifying quantum chromodynamics as they go) and Cline et al (1997, keeping to standard physics, but addressing only a subset of 11 GRBs with durations less than 0.1 s) have put these into the pool again. Moderate fluence ones would have to be less than 30 pc away, even with 100% efficiency for conversion to gamma rays, and how firmly you want to exclude them depends on how firmly you believe that the classic GRBs are all the same sort of beast.…”
Section: And All the Restmentioning
confidence: 99%
“…For the majority of the short-duration GRB population, however, there is simply not enough evidence to determine their origin unambiguously. Hawking radiation from primordial black holes (PBH) was one of the very first explanations proposed for cosmic GRBs (Hawking 1974), and it continues to be proposed today (Cline & Hong 1996;Cline et al 1997Cline et al , 1999Cline et al , 2003Cline et al , 2005Czerny et al 2011). The PBH lifetime and burst duration depend on its mass, so that PBHs bursting today have similar masses and durations, and release similar energies, making them in essence "standard candles."…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many attempts to find evidence for the existence of PBH bursts to date have been based mainly on the spatial distribution and time histories of a subset of short bursts (Cline & Hong 1996;Cline et al 1997Cline et al , 1999Cline et al , 2003Cline et al , 2005Czerny et al 2011). Other search methods have employed atmospheric Cherenkov detectors (Porter & Weekes 1977Linton et al 2006;Tesic & VERITAS Collaboration 2012;Glicenstein et al 2013), air shower detectors (Fegan et al 1978;Bhat et al 1980;Alexandreas et al 1993;Amenomori et al 1995;Abdo et al 2015), radio pulse detection (Phinney & Taylor 1979;Keane et al 2012), spark chamber detection (Fichtel et al 1994), and GRB femtolensing (Barnacka et al 2012).…”
Section: Introductionmentioning
confidence: 99%